External shocks and policy alternatives in small open economies: The case of El Salvador - Morley, Samuel; Piñeiro, Valeria; Robinson, Sherman (International Food Policy Research Institute, 2011)
In this paper we used a dynamic, regionalized computable general equilibrium (CGE) model to analyze the effect of various negative balance of payments shocks on output and employment and the effect of different alternative investment strategies on growth. The model shows clearly how sensitive El Salvador is to remittance or terms of trade shocks. Each 10 percent reduction in remittances lowers gross domestic product (GDP) by 0.2 percent and household consumption by 1.4 percent, with the cost rising as the shock intensifies. Any negative balance of payments shock forces a reduction in absorption, production, and employment and a real devaluation. Because El Salvador's economy is dollarized, that real devaluation can only come about through a fall in domestic prices brought about by recession. We show that the impact of the shock on output depends on how flexible wages are—the impact is smaller when real wages are flexible and greatest when they are fixed in dollars.We used the CGE model to analyze alternative investment strategies for increasing the growth rate. The investment share of GDP is low, and the model makes it clear that without some strategy for increasing investment, the economy's overall growth rate is likely to remain low. We hypothesized two alternative growth rates for investment, both associated with an increase in exogenous technical change. Both strategies require a marginal increase in the share of output devoted to investment. We also showed that if El Salvador can increase the investment share from 15.5 percent to just 16 percent over five years by producing a growth rate in investment of 8 percent per year, and if that increase produces a 1 percent increase in the rate of technical change in all sectors, then the growth rate of the economy will practically double, rising from 2.85 percent to 4.95 percent per year. There are equally favorable effects on employment for unskilled labor and on wages for skilled labor.